Wage cyclicality: Evidence from Spain using social security data - Jorge De la Roca (SERIEs - Journal of the Spanish Economic Association, 2014)
Using longitudinal social security data, this study finds evidence of weak real wage cyclicality in Spain throughout 1988 - 2011. The baseline estimate of a 0.4 % increase in wages in response to a one percentage point decline in the unemployment rate lies in the lower bound of available estimates for developed countries. Wage cyclicality in a rigid labour market like Spain is mainly driven by workers under temporary contracts and newly-hired workers. I calculate the cyclicality of the net present value of wages in new matches - the relevant piece of information for firms posting vacancies, but a rarely available measure - and find that it is well approximated by the cyclicality of wages for newly-hired workers.
Keywords: C24; E32; J31; 330; Wage cyclicality; Labour market duality; Social security data; Censoring